Stem Cells: Biology and Engineering (Innovations in Cancer Research and Regenerative Medicine,, 2018)
This new series, based on a bi-annual conference and its topics, represents a major contribution to the emerging science of cancer research and regenerative medicine. Each volume brings together some of the most pre-eminent scientists working on cancer biology, cancer treatment, cancer diagnosis, cancer prevention and regenerative medicine to share information on currently ongoing work which will help shape future therapies. These volumes are invaluable resources not only for already active researchers or clinicians but also for those entering these fields, plus those in industry. Stem Cells: Biology and Engineering is a proceedings volume which reflects papers presented at the Innovations in Regenerative Medicine and Cancer Researchconference; taken with its companion volume Tissue Engineering and Regenerative Medicine it provides a complete overview of the papers from that meeting of international experts. .